Impact of InGaAs carrier collection quantum well on the performance of InAs QD active region lasers fabricated by diblock copolymer lithography and selective area epitaxy. (14th January 2019) - Kim, Honghyuk; Wei, Wei; Kuech, Thomas F; Gopalan, Padma; Mawst, Luke J
Abstract: Quantum dot (QD) laser diodes, where the active region consists of wetting-layer-free InAs QDs, were demonstrated by block copolymer (BCP) lithography and subsequent selective area metal-organic vapor phase epitaxy, which results in the QD density of ∼4 × 10 10 cm 2 . In this work, we show that an In0.1 Ga0.9 As QW located in close proximity to the wetting-layer-free InAs QDs leads to an enhanced carrier injection into the QDs, allowing for lasing at room temperature (RT). Devices employing InAs QDs grown with and without In0.1 Ga0.9 As QW carrier collection layer exhibit lasing at 80 K, while only the lasers grown with the In0.1 Ga0.9 As QW exhibits lasing at RT. Driving current-dependent electroluminescence measurements reveals a low carrier injection into the QDs in the device grown without In0.1 Ga0.9 As QW carrier collection layer. In addition, the appearance of lasing emission, corresponding to high energy transitions, indicates a relatively flat gain profile for this InAs QD active region grown by SA-MOVPE. In addition, EL measurements at 80 K on devices employing varying thickness ( d InAs ) QDs indicate the peak emission wavelength varies from 920 nm ( d InAs ∼ 1.5 nm) to 974 nm ( d InAs = 3 nm), although the devices employing d InAs ∼ 3 nm did not exhibit lasing, possibly because of a significant degree of strain relaxation for this QD thickness.